2011
DOI: 10.1029/2010jd015305
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the raindrop size distribution for freezing precipitation observed in southern China

Abstract: [1] Freezing precipitation (i.e., freezing rain or freezing drizzle) is an extremely hazardous weather that can cause severe socioeconomic loss and compromise human safety. To better document and understand the microphysics of this type of precipitation, drop size spectra were collected with an optical disdrometer during a freezing precipitation event on 27 January 2008 in southern China. The drop size distribution (DSD) characteristics, the correlations between the shape (m), slope (L), and intercept (N 0 ) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…In particular, Chen et al (2011) found a relatively large number of small drops, whereas Iwai (1970) found a dearth of small drops and an abundance of large drops when compared with the expected Marshall-Palmer distribution. Given the relatively low precipitation rates typically associated with freezing rain, often substantially less than 10 mm h −1 , and the relatively shallow distances over which the spectra can evolve, such widely different results likely reflect substantial differences in the initial particles aloft.…”
Section: Formation Of Precipitation Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Chen et al (2011) found a relatively large number of small drops, whereas Iwai (1970) found a dearth of small drops and an abundance of large drops when compared with the expected Marshall-Palmer distribution. Given the relatively low precipitation rates typically associated with freezing rain, often substantially less than 10 mm h −1 , and the relatively shallow distances over which the spectra can evolve, such widely different results likely reflect substantial differences in the initial particles aloft.…”
Section: Formation Of Precipitation Typesmentioning
confidence: 99%
“…As well, if large drops are observed in freezing rain events, there must be a sufficiently warm and/or deep melting layer for those to occur; otherwise, a kernel of ice will remain within the hydrometeor by the time it reaches the subfreezing layer and it would freeze into an ice pellet or a liquid core pellet. The two studies, Iwai (1970) and Chen et al (2011), examined events with only freezing rain; a later part of this article discusses size spectral features when combinations of precipitation types, including freezing rain, occur.…”
Section: Formation Of Precipitation Typesmentioning
confidence: 99%
“…Characteristics of DSDs in different continental locations from tropics to midlatitudes along with different disdrometers have been well documented. For example, in Darwin, Australia (Penide, Kumar, et al, ; Penide et al, ; Thurai et al, ), the coast of India (Harikumar et al, ; Radhakrishna et al, ), northeastern Brazil (Tenório et al, ), Singapore (Kumar et al, ), Oklahoma (Cao et al, ), and south and east China (Chen et al, , ; Wen et al, ). Characteristics of DSDs in a few maritime locations are also reported; there were the Tropical Ocean and Global Atmosphere Coupled Ocean‐Atmosphere Response Experiment carried out in Pacific (Atlas et al, ) and the research on the summer season DSD differences between Palau and Taiwan in western Pacific reported by Seela et al ().…”
Section: Introductionmentioning
confidence: 99%
“…As the most fundamental microphysical property of precipitation, raindrop size distribution (DSD) represents the number of drops as a function of diameter in a given sample. It has been adequately demonstrated that the knowledge of DSD is essential for a better understanding of microphysical processes in the generation of precipitation particles (e.g., Chen et al, 2011Chen et al, , 2013Niu et al, 2010;Radhakrishna et al, 2009;Tang et al, 2014) as well as a fundamental quantity in radar meteorology and other remote sensing applications (Anagnostou et al, 2008;Munchak et al, 2012;Viltard et al, 1998;Williams et al, 2007). For instance, modeled DSD parameters are widely used in rainfall estimation algorithms of the National Aeronautics and Space Administration Tropical Rainfall Measuring Mission precipitation radar (PR; Iguchi et al, 2000;Kozu et al, 2009) and in the current Global Precipitation Measurement (GPM) Dual-frequency PR (DPR; Hou et al, 2008;Liao et al, 2014;Nakamura & Iguchi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, DSD observations have also been conducted over a variety of regions in China using filter papers and optical disdrometers (Chen et al, , , ; Niu et al, ; Tang et al, ; Wang, Yin, & Zhai, , and references herein; Wen et al, ). These studies have improved our understanding of the microphysical properties of precipitation over various areas in China.…”
Section: Introductionmentioning
confidence: 99%